A study on the sport demonstration system based on three-dimensional reconstruction - Geng, L.; Li, J. (MATEC Web of Conferences, 2015)
Sport demonstration system can help improve the effect of teaching and training in physical sports. In practical athletic training, the two-dimensional sport demonstration system has been widely applied. However, there`s certain visual deficiency existing in the accurate motion positioning and the kinematic analysis of the two-dimensional sport demonstration system. In order to help coaches and students clearly understand the subtle points of physical sports in an all-around way, this paper studied the sport demonstration system based on three-dimensional reconstruction. It analyzed the camera imaging principle and the three-dimensional reconstruction principle in theory, and has reached the conclusion that the key in the three-dimensional reconstruction of two-dimensional digital video lies in the segmentation of two-dimensional videos. The selective analyses of this paper are about the three-dimensional reconstruction of segmented images. Based on this reason, this paper proposed the calibration technique of application camera and the means of stereo matching, so as to achieve the precise matching of accurate space ray equation and corresponding pixels. In the final part, this paper took diving as the example and designed the sport demonstration system composed of analysis module, three-dimensional simulation, interface module and data management module on basis of three-dimensional reconstruction.